Prototipo de bastón inteligente para invidentes (Journal on studies and research of academic knowledge, 2015)
Generally, a non-sighted to move in unknown places uses the white cane, however this does not detect obstacles that are from the waist up, so in this project has proposed to develop a prototype that can perform the tasks that the . traditional cane can not, using a technology that is able to detect various obstacles that are outside the range of traditional cane and notify to the user through vibrations when the obstacle is close to him. The objetive of this work was the development of an intelligent cane's prototype for the blind through applied research. Considering the above, the smart cane's prototype was designed taking into account the following steps: a). Obstacle detection system from sensor HY-SRFOS ultrasound. b). Remote sensing system c). Communication system via the Ublox NEO6m and shield SIM900 GPRS modules. At each stage tests were performed using codes programmed Arduino One platform in order to analyze and check the operation and working range of each module. The total of tests were seven, getting the best results for each test, which integrated get an economically accessible sophisticated equipment, using high quality components and technology applicable for any type of cane, independent of the material that composes it.
Keywords: modules; remote sensing system; Arduino; Hy SRFOS; GPRS shield; Neo6m